The wisdom of the hive : the social physiology of honey bee colonies - Seeley, Thomas D. (Harvard University Press, 1995)
This book describes and illustrates the results of more than fifteen years of elegant experimental studies conducted by the author to investigate how a colony of bees is organized to gather its resources. The results of his research - including studies of the shaking signal, tremble dance, and waggle dance - offer the clearest, most detailed picture available of how a highly integrated animal society works.